Penguatan Konsep Dasar Matematika Pada Kelompok Kerja Guru Gugus XIV Kecamatan Bacukiki Barat Kota Parepare - Zaid Zainal (Publikasi Pendidikan, 2018)
The 2013 curriculum requires the teaching of each subjects are integrated, known,. This means that on one theme may link some subjects in it. After evaluating in implementation, curriculum  2013 revised edition provides the exceptions of teaching mathematics to be taught in separate. The main problems faced by teachers, especially in the teaching of mathematics are; less mastering the basic concepts of mathematics, there are still materials that do not know taught and often there are math problems that are difficult to solve. This devotional activity aims to help upper class teachers in the sub district of Bacukiki Town of Parepare (partner)  in understanding the basic concepts of mathematics, helping to solve problems that are considered difficult and difficult math material taught.Activities in the form of workshops reinforcement of mathematical material on groups of partner teachers. Interactive teaching methods, joint research and self-assignment proved to improve knowledge and understanding of basic mathematical concepts for partner teachers.